Moral Value Comparison in Indonesian and British Folklores in Children Literature - Silalahi, Ronald Maraden Parlindungan; Juliana, Rika; Citradi, Hanson; Cecilia, Cecilia (Anglophile Journal, 2021)
Folklore is a story created by the community whose existence is intended to entertain children through stories containing moral values to have an essential role for children. It usually based on the culture of those who created them, making folklores from different areas unique in their ways, including the morals they teach. This article is qualitatively aimed to analyse and compare folklores from both Indonesia and Britain, finding similarities and differences in the moral values they teach. This research is directed to compare folklore originating from Indonesia and England because they both have different cultural backgrounds and analyse how each culture can differentiate between two similar stories. The new criticism theory is applied during the comparison process, divided into first analysing the story, ending with the morals that the story attempts to teach. The result of this study shows that, despite the difference in culture between the two cultures, their folklores can teach the same morals, as shown by “Saudagar yang Kikir” dan “The Old Witch”. On the other hand, ‘Legenda Batu Menangis’ and ‘Cap O’ Rushes’ contain different moral values and are more difficult to compare, despite both having familial themes.. Keywords: Children Literature, Indonesian and British Folkflores, Literature Study